Extent of induced abortions and occurrence of complications in Kinshasa, Democratic Republic of the Congo - Daniel Katuashi Ishoso; Antoinette Kitoto Tshefu; Thérèse Delvaux; Yves Coppieters (BMC, 2019)
Abstract Background Due to a lack of relevant data on induced abortions in the Democratic Republic of the Congo (DRC) as well as the persistence of maternal deaths in the country, this study aims to analyse the extent of induced abortions and occurrence of complications in Kinshasa. Methodology This cross-sectional study was conducted with a sample of 460 women who were interviewed about their experiences as females, and provided information of 1444 women of childbearing age living in Kinshasa. Respondents' households were selected to represent the five types of residential quarters in Kinshasa, differentiated by cultural, socioeconomic, and infrastructural characteristics. Information was collected using a survey form and analyzed. Results Among all confidantes included in the study, 5.5% (95% CI: 4.4-6.8%) had induced abortions during 2015, a rate of 55.0 abortions per 1000 women of childbearing age. This practice was significantly performed amongst single/separated/divorced women; those without formal education, or primary-school education, and women who consumed excessive alcohol. Most abortions were induced by the administration of high doses of medication, by the women themselves or by health workers. A percentage of 51.9% (95%CI: 40.4-63.3%) of induced abortions led to complications, which were predominantly haemorrhagic. Moreover, 39% of patients had a complication for which they sought care, and of whom 12.5% had genital trauma or uterine perforation/intestinal necrosis. Conclusion Induced abortion is a public health problem in Kinshasa due to its frequency of practice, the complications that occur, and the absence of major surgeries in the health care package offered by the health centres or dispensaries that also provide the treatment of some serious complications. Thus, there is a need to focus on the enhancement of the health care package offered by health centres to include appropriate measures in favour of maternal health.